Pleiotropic and novel phenotypes in the Drosophila gut caused by mutation of drop-dead. (February 2018) - Conway, Sean; Sansone, Christine L.; Benske, Anika; Kentala, Kaitlin; Billen, Johan; Vanden Broeck, Jozef; Blumenthal, Edward M.
Graphical abstract: Highlights: Adult drop-dead ( drd ) mutant Drosophila lack a peritrophic matrix (PM). drd is expressed in the anterior cardia in late pupal and adult flies. drd in the cardia is correlated with formation of the PM and normal defecation rate. Adult knockdown of drd eliminates the PM without affecting defecation or survival. Abstract: Normal gut function is vital for animal survival, and deviations from such function can contribute to malnutrition, inflammation, increased susceptibility to pathogens, diabetes, neurodegenerative diseases, and cancer. In the fruit fly Drosophila melanogaster, mutation of the gene drop-dead (drd) results in defective gut function, as measured by enlargement of the crop and reduced food movement through the gut, and drd mutation also causes the unrelated phenotypes of neurodegeneration, early adult lethality and female sterility. In the current work, adult drd mutant flies are also shown to lack the peritrophic matrix (PM), an extracellular barrier that lines the lumen of the midgut and is found in many insects including flies, mosquitos and termites. The use of a drd-gal4 construct to drive a GFP reporter in late pupae and adults revealed drd expression in the anterior cardia, which is the site of PM synthesis in Drosophila . Moreover, the ability of drd knockdown or rescue with several gal4 drivers to recapitulate or rescue the gut phenotypes (lack of a PM, reduced defecation, and reduced adult survival 10–40 days post-eclosion) was correlated to the level of expression of each driver in the anterior cardia. Surprisingly, however, knocking down drd expression only in adult flies, which has previously been shown not to affect survival, eliminated the PM without reducing defecation rate. These results demonstrate that drd mutant flies have a novel phenotype, the absence of a PM, which is functionally separable from the previously described gut dysfunction observed in these flies. As the first mutant Drosophila strain reported to lack a PM, drd mutants will be a useful tool for studying the synthesis of this structure.